Information retrieval : 23rd China conference, CCIR 2017, Shanghai, China, July 13-14, 2017, Proceedings /: 23rd China conference, CCIR 2017, Shanghai, China, July 13-14, 2017, Proceedings. (2017) - Unknown
No abstract available